2019
DOI: 10.3390/medicina55120775
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Primary Duodenogastric Bile Reflux on the Presence and Density of Helicobacter pylori and on Gastritis in Childhood

Abstract: Background and Objectives: Although there are many studies that investigate the relationship between duodenogastric reflux (DGR) and Helicobacter pylori in adult patients, the reported data are contradictory. In addition, there are very few studies in the literature investigating the relationship between DGR and H. pylori in the pediatric age group. In the present study, we investigated the effect of primary DGR on H. pylori and gastritis. Materials and Methods: A total of 361 patients who were referred to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 24 publications
0
20
0
4
Order By: Relevance
“…Duodenogastric reflux (DGR, bile reflux) consists of a retrograde passage of alkaline duodenal and pancreatic content into the stomach, which can lead to mucous barrier disruption and direct chemical damage to the surface gastric epithelium. DGR is common after gastric surgery, cholecystectomy and pyloroplasty, but it can also occur due to antroduodenal motility disorder (primary DGR) (1,2). Primary bile reflux does not have a standardized diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Duodenogastric reflux (DGR, bile reflux) consists of a retrograde passage of alkaline duodenal and pancreatic content into the stomach, which can lead to mucous barrier disruption and direct chemical damage to the surface gastric epithelium. DGR is common after gastric surgery, cholecystectomy and pyloroplasty, but it can also occur due to antroduodenal motility disorder (primary DGR) (1,2). Primary bile reflux does not have a standardized diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, Vere et al [15] found biliary reflux more commonly in the elderly (50–80 years) and attributed this finding to a higher incidence of stomach surgery, which is a risk factor for DGR in these patients. In a study by Agin et al [6] on children, DGR was demonstrated to be significantly more common in older children. Likewise, in the present study, the mean age of patients with biliary reflux was found to be significantly higher than that of patients without reflux.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few studies investigating the relationship between DGR and H. pylori in adults, but a paucity of studies involving children. Most of the studies on adults and few studies on children propose that the presence of DGR decreases H. pylori colonization, while the presence of H. pylori increases the prevalence of DGR by impairing antroduodenal motility [1, 2, 6, 8-10]. The aim of the present study was to investigate the relationship between primary DGR and H. pylori prevalence , degree of colonization, and the presence and severity of gastritis in the pediatric population.…”
Section: Introductionmentioning
confidence: 98%
“…In this case, the presence of bile salts would be responsible for the alkaline pH observed in post-anesthetic evaluations. Although not performed in this study, the resulting analysis of gastric juice with pHmetry would be interesting to demonstrate the presence and concentration of bile salts, diagnosing duodenogastric re ux [31][32][33].…”
Section: Discussionmentioning
confidence: 99%